The global system of international migrations, 1900 and 2000: a comparative approach - Giovanni Gozzini (Journal of Global History (2006) 1, pp. 321-341, 2006)
The aim of this paper is to compare international migrations in two different periods of history, both of them marked by a rapid increase in the trend: the first period runs from 1870 to 1914, and the second from 1965 to 2000. Historical and current migration system maps are compared, together with their different combinations of push and pull factors, and of coerced and free migrations. The various repercussions that international migrations have on demographic structure and on the economic systems of the sending and receiving countries are counterbalanced by a number of significant analogies that occur at the microlevel (individual and community) of the mechanisms governing the decision to migrate, and of migrants' identities and behavioural patterns. The final section shows that migrants in both periods retain ties to both their old and new countries (as indicated by remittances and return migration), despite the major obstacles that stand in the way of the free circulation of international migrants today. This suggests that an analysis of migration systems, emphasizing ongoing interactions of various sorts between sending and receiving areas, is superior to either a model based on the presumption that assimilation will occur over time or one which presumes an irreducible `multiculturalism'.